NUMERICAL STUDY OF VISCOUS FLUID DAMPERS (VFDs) APPLICATION AS PASSIVE CONTROL ON SEISMIC RESISTANCE ECCENTRICALLY BRACED FRAME - RAHMAN DALIMUNTHE (NIM : 25007309); Pembimbing : Prof. Dr. Ir. Herlien D. Setio, ABDUL
In recent years, control systems are widely used in structures, especially buildings and bridges. The use of control systems on the structure is intended to be more adaptive and responsive against dynamic loading due to earthquake or wind. The control systems are categorized into passive and active control. Passive control system worked without using external energy and not at risk resulted in unstable state of the structure. This system is considered capable of controlling the response of the structure on certain restrictions. While active control system using additional external energy to resist dynamic loads through the control forces generated by the control algorithm was applied to devices. This system is also equipped with sensors and actuators. This thesis discussed the comparison of the performance of steel frame structures without control system and steel frame structure with control system which is analyzed numerically. Eccentrically braced frames is the type of structural system, while the control system is a viscous fluid dampers (VFDs) which is part of the passive controls. For example, three-stories and ten-stories building are studied. Application of control system is provided through partial substitution segment of bracing with VFDs. Substitution was carried out to see the performance and effectiveness of VFDs on eccentrically braced frames induced by Elcentro and Northridge earthquakes. The analysis results showed that the application of VFDs on the eccentrically braced frame system will be more effective in reducing response of the structure (displacement, velocity and acceleration) compared with eccentrically braced frame system without VFDs. Reduction of the structural response is due to the large of damping energy that can be dissipated by devices through the action of viscosity when the earthquake is occurred. In addition, the application of VFDs on the structural system which is dominated by the first mode showed better performance when compared with the structural system that is dominated by higher modes.